2021
DOI: 10.1155/2021/9996857
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Three-Dimensional Morphological Differences in the Mandible between Skeletal Class I and Class II with CBCT Fixed-Point Measurement Method

Abstract: This study was aimed at determining the three-dimensional differences in the mandible morphology between skeletal class I and II patients, at exploring the pathogenic mechanisms and morphological characteristics of skeletal class II, and at providing clinical references. The subjects were assigned to two groups according to the size of ANB angle: skeletal class I ( 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In the present study, ramal height (Ar-Go) was smaller in the Class II skeletal relationship compared with the Class I and Class III groups, whereas it was similar between Class I and Class III subjects. This was in agreement with Dong et al, 33 who found that patients with a Class II skeletal relationship tended to have smaller ramal height (Co-Go) when compared with Class I subjects.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, ramal height (Ar-Go) was smaller in the Class II skeletal relationship compared with the Class I and Class III groups, whereas it was similar between Class I and Class III subjects. This was in agreement with Dong et al, 33 who found that patients with a Class II skeletal relationship tended to have smaller ramal height (Co-Go) when compared with Class I subjects.…”
Section: Discussionsupporting
confidence: 92%
“…The current study observed that ramal height was shorter in individuals with a Class II skeletal relationship, whereas mandibular body length was longer in those with a Class III skeletal relationship, in comparison to Class II. These results were in line with earlier investigations, such as those conducted by Dong et al and Gasgoos et al [20,21]. Furthermore, the present study noted that the mandible exhibited greater size within the Class III group, a finding consistent with previous research [21][22][23].…”
Section: Discussionsupporting
confidence: 94%
“…The growth of the ramus height is mainly determined by the new bone deposition on the mandibular condyle, which involves highly complicated environmental and genetic factors (34,35). The insufficient growth of the mandibular ramus is usually associated with a reduced posterior facial height, divergent growth pattern, and skeletal class II relationship (36,37), whereas significant condylar and ramus growth could prevent backward rotation of the mandible (38).…”
Section: Discussionmentioning
confidence: 99%